Pengaruh Intensitas Penggunaan Media Internet Terhadap Perilaku Belajar Siswa - Saiful Haq (Millah: Journal of Religious Studies, 2015)
Internet has been exploited and used by students every day. Internet presence  brings much convenience to users. However, the Internet also have a negative effect on students. In the negative effects arising from the use of the internet, the necessary countermeasures in order not to disrupt the learning activities of students. This study aims to determine the effect of Internet use on student learning behavior. This research is the primary data with quantitative approach. The number of samples used, there are 98 students of class XI MAN Purworejo. Samples were then given questionnaires that have been tested for validity and reliability. Analysis of the data used is descriptive analysis to determine the frequency, percentage, mean, median, and mode. The statistical test used was chi-square to determine whether there is the effect of Internet use on student learning behavior. The analysis showed that 50% of students are heavy users with an average of 1.77 hours per day usage. 31.6% of students open social media more than once a day. 45.9% Based on the learning behavior of students have learned good behavior. The findings of this study showed no effect of the use of the Internet by students’ learning behavior (p=0.89). The negative effect is felt most students is to forget the time. Ways to overcome them can Cognitive-behavioral Therapy.